Examining knowledge transfer using SECI model as lenses : A study of interaction among local Malaysian entrepreneurs and Indonesian cross-border entreprenuers in cross-border Serikin weekend market - Hutasuhut, Ida Juliana; Usop, Hasbee; Shahren, Ahmad Zaidi Adruce; Sabil, Surena; Kasa, Mark (2017)
Little attention has been given to the study on the impact of local Bidayuh entrepreneurs in Serikin weekend market despite the tremendous presence of cross-border Indonesian entrepreneurs. The objective of this study is to examine the knowledge transfer that may have happened between the entrepreneurs between two countries during their interaction every weekend by using SECI Model as lenses. Qualitative phenomenological study was conducted to answer the research questions. A total of thirty local/Bidayuh entrepreneurs were purposively selected to participate in this study in order to get rich data. Participants were interviewed using semi-structured interview questions and the data were analyzed using content analysis approach. This study concluded that the presence of Indonesian-cross border entrepreneur helps to improve the economy of the villagers, open the opportunities for business partner, provide role model in doing business, and bring revenue to the government. However, although the business-activities in Serikin market have been going on for decades, the transfer of knowledge among fellow entrepreneurs (between Indonesian cross-border entrepreneurs and Bidayuh-entrepreneurs) is still very minimal. This is due to the very limited time and space for them to have interaction. Recommendations to improve this situation are provided at the end of this paper.